Clinical Characteristics and Management of Patients With McCune-Albright Syndrome With GH Excess and Precocious Puberty: A Case Series and Literature Review - Zhai, Xiao; Duan, Lian; Yao, Yong; Xing, Bing; Deng, Kan; Wang, Linjie; Feng, Feng; Liang, Zhiyong; You, Hui; Yang, Hongbo; Lu, Lin; Chen, Shi; et al. (Frontiers in Endocrinology, 2021)
Background McCune-Albright syndrome is a rare disorder characterized by fibrous dysplasia, café au lait skin spots, and hyperfunctioning endocrinopathies. The coexistence of precocious puberty and growth hormone excess in McCune-Albright syndrome is rare. Both conditions can manifest as accelerated growth, and treatments can be more challenging for such patients. This study aimed to describe the clinical manifestations of combined GH excess and PP in the context of McCune-Albright syndrome and analyze the clinical features and treatments of these patients. Method Clinical data from 60 McCune-Albright syndrome patients from Peking Union Medical College Hospital were obtained. The demographic characteristics, growth hormone, insulin-like growth factor-1, prolactin, alkaline phosphatase, and sex hormone levels; growth velocity; and bone age data were obtained. The growth velocity Z-score, bone age over chronological age ratio, and predicted adult height Z-score were calculated before and after treatment. Published studies and case reports were systemically searched, and data on demographic, clinical, and biochemical characteristics and treatment outcomes were obtained. Results We reviewed seven patients among 60 McCune-Albright syndrome patients at Peking Union Medical College Hospital (5 female) and 39 patients (25 female) from the published literature. Six of the seven patients from Peking Union Medical College Hospital and half of the patients from the published studies were pediatric patients. These patients had increased growth velocity Z-scores and bone age over chronological age ratios. After good control of both conditions, the growth velocity Z-score and bone age over chronological age ratio decreased significantly, and the predicted adult height Z-score increased. The final heights and predicted adult height Z-scores were not impaired in patients with gigantism. All the patients had craniofacial fibrous dysplasia associated with optic and otologic complications. Conclusion McCune-Albright syndrome with growth hormone excess and precocious puberty is more common in girls. Patients have accelerated linear growth and advanced skeletal age, and early and good control of both conditions leads to a reduced growth velocity and stabilized bone age. The predicted adult and final heights are not negatively affected when growth hormone excess is diagnosed in pediatric patients.